Power saving MAC protocols in wireless sensor networks: a survey - Rafael Souza Cotrim; João Manuel Leitão Pires Caldeira; Vasco N. G. J. Soares; Youcef Azzoug (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In a wireless sensor network, energy is almost always the greatest limitation. Energy sources are restricted in many of the environments where nodes are deployed, limiting them to the use of batteries for power. Therefore, conserving energy is supremely important, however, such a task poses many challenges to hardware and protocol design. One of the greatest problems faced is reducing the energy consumption of the communications systems, which represents a substantial amount of the total consumption. This paper surveys the most recent schemes designed to reduce the communications module energy consumption with a focus on novel MAC protocols for ad-hoc wireless sensor networks. It initially describes the many challenges involved, then it analyses each protocol individually. Finally, the presented protocols are compared and the issues that remain open are raised for further research.